Can adoption of chemical pesticide-free farming practices benefit to farmers? An empirical study in shallot production in Central Java, Indonesia - Tinaprilla, Netti; Utami, Anisa Dwi; Suprehatin (Jurnal Manajemen & Agribisnis, 2022)
This study aims to provide empirical evidence in the shallot production in Indonesia, what drives farmers to adopt chemical pesticide-free production as sustainable agricultural practices and its impacts on farmers’ income. By using national agricultural survey in 2014, this study employed logit regression and regression analysis to estimate the determinants and impacts of adoption of chemical pesticide-free farming practices among shallot farmers in Central Java. The results of a logit regression model showed that level of education, type of land ownership, participation in farmers group, source of fund, certified seed cost, and cost production were significantly associated with decisions to adopt chemical pesticide-free farming practices. The results of a regression model showed that farmers who adopted chemical pesticide-free farming practices had higher income. Aside the chemical pesticide-free adoption factor, the results showed that farmers’ income from shallot farming were influenced by level of education, harvested area, type of land ownership, cooperative membership, access to credit, access to extension services, and cost of certified seed. Future research may consider the different level of usage of non-chemical inputs among shallot farmers as the adoption is a process and dynamic, taking into account both other potential determinants of adoption and other potential factors affecting farm profitability, and focusing on shallot traders, wholesalers, retailers, and consumers. Keywords: agricultural production, famers income, pesticide-free, shallot, sustainable agricultural practice